Real-world effectiveness of COVID-19 vaccines: a literature review and meta-analysis - Zheng, Caifang; Shao, Weihao; Chen, Xiaorui; Zhang, Bowen; Wang, Gaili; Zhang, Weidong (International journal of infectious diseases, 2022)
•This study reports COVID-19 vaccine effectiveness (VE) in real-world settings.•COVID-19 VE for fully and partially vaccinated individuals.•COVID-19 VE for healthcare workers, the elderly, and adults.•The effectiveness of different COVID-19 vaccine brands. To estimate the coronavirus disease 2019 (COVID-19) vaccine effectiveness (VE) against concerned outcomes in real-world settings. Studies reporting COVID-19 VE from August 6, 2020 to October 6, 2021 were included. The summary VE (with 95% confidence intervals (95% CI)) against disease related to COVID-19 was estimated. The results were presented in forest plots. Predefined subgroup analyses and sensitivity analyses were also performed. A total of 51 records were included in this meta-analysis. In fully vaccinated populations, the VE against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, COVID-19-related hospitalization, admission to the intensive care unit, and death was 89.1% (95% CI 85.6–92.6%), 97.2% (95% CI 96.1–98.3%), 97.4% (95% CI 96.0–98.8%), and 99.0% (95% CI 98.5–99.6%), respectively. The VE against infection in the general population aged ≥16 years, the elderly, and healthcare workers was 86.1% (95% CI 77.8–94.4%), 83.8% (95% CI 77.1–90.6%), and 95.3% (95% CI 92.0–98.6%), respectively. For those fully vaccinated against infection, the observed effectiveness of the Pfizer-BioNTech vaccine was 91.2% and of the Moderna vaccine was 98.1%, while the effectiveness of the CoronaVac vaccine was found to be 65.7%. The COVID-19 vaccines are highly protective against SARS-CoV-2-related diseases in real-world settings.